Islam Dan Pemberdayaan Masyarakat Perspektif Hadis - Bagus, Sobirin (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2021)
The purpose of this paper is to make an inventory of the hadiths of the prophet relating to community empowerment, to know his takhrij, and to examine the contents of the hadiths about community empowerment. The method used is a thematic method with a literature research approach by examining the hadiths from capital sources. The conclusion is that the results of an inventory of the hadiths about community empowerment were obtained 129 hadiths from 18 hadith books. Of these 129 hadiths, the writer takes the most relevant hadiths, namely the hadith from Abud Daud Number 1398 on economic empowerment and the hadith from Abu Daud number 18723. Community economic empowerment during the time of the prophet is in the hadith of Abu Daud, while the empowerment of Ahmad's hadith. Meanwhile, community empowerment during the caliphate: education, monotheism, morals, worship, health. The Caliphate then built mosques, appointed teachers, taught the contents of the Al-Quran and other Islamic teachings. The next caliphate: the freedom to teach according to the desired place. And the last Caliphate focused on security and peace. The relevance of community empowerment in educational institutions is very clear amid diversity but it is not yet maximally and evenly distributed. Both in terms of community empowerment in the field of science and community empowerment in the field of economy and welfare.